Sub-critical water pyrolysis of oil palm trunk for production of bio-oil and solid product - Muda, Noor Azura (2018)
Oil palm tree is a commercial crop in Malaysia producing millions of tonnes of unused oil palm trunk (OPT) waste during replanting process which is done in large scale every 25 to 30 years. The inner region of OPT was unutilized due to high moisture content which make it easy to rot. In this study, water at sub-critical state was utilized to produce bio-oil and solid product from the inner region of OPT. The objectives for this study are to evaluate the effect of reaction temperature and time on the yield of bio-oil and solid product produced, to determine the optimum condition (reaction temperature and time) for the production of bio-oil and solid product, and to characterize the bio-oil and solid product obtained. In order to determine the best OPT for the production of bio-oil and solid product from the inner region of OPT, 21 and 35 year old OPTs were used. Each OPT were divided into two parts, namely top and bottom parts. OPTs were then cut into small size and loaded into a reactor. The reactor was then immersed in a molten salt bath for sub-critical water (Sub-CW) reaction. The reaction was carried out in a temperature range between 100°C-370°C with 10°C intervals and reaction time was varied between 0.1 to 20 minutes. It was found that, the best OPT for production of bio-oil and solid product is from the 21 years old OPT. In the 21 years old OPT, the optimum condition for the highest production yield of bio-oil was 27.5% kg/kg-dry OPT (OPT21T, 340ºC, 5 min) and 30.1% kg/kg-dry OPT (OPT21B, 330ºC, 5 min). The highest Higher Heating Value (HHV) of bio-oil was 33,200kJ/kg (OPT21T, 350ºC, 5 min) and 26,400kJ/kg (OPT21B, 340ºC, 5 min). The best HHV of solid product was 31,000kJ/kg (OPT21T, 370ºC, 5 min) and 32,400kJ/kg (OPT21B, 340ºC, 5 min). The particle size of solid product at optimum condition was 20m and 17m for OPT21B and OPT21T, respectively. The main chemical compound found in bio-oilwere phenol, 2-methoxy-phenol, 4-ethyl-2-methoxy-phenol, and 2,6- dimethoxy- phenol. These results show that Sub-CW reaction is technically feasible in producing bio-oil and solid product from OPT.